Analisis Tingkat Kesehatan Bank Jatim dengan Menggunakan Metode RGEC Periode 2022-2023 Sebagai Dasar Pengambilan Keputusan - Siwi, Ghea Nada Ramadhani Putri; Sodik, Sodik; Fatoni, Irfan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The purpose of this study is to determine the health level of Bank Jatim using the RGEC method as a basis for decision-making. The type of research used in this study is descriptive with a quantitative approach. Secondary data in this study is the published Annual Financial Report of Bank Jatim for the 2022-2023 period. The data analysis method used is financial statement analysis using the RGEC method. Where the Risk Profile is measured using the NPL and LDR indicators, GCG is measured using the Self-Assessment indicator, Earnings are measured using the ROA, ROE, NIM and BOPO indicators, Capital is measured using the CAR indicator. The results show that Bank Jatim's NPL in 2022 is in the